2018
DOI: 10.3348/kjr.2018.19.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Plaque Stiffness Measured with Supersonic Shear Imaging and Its Correlation with Serum Homocysteine Level in Ischemic Stroke Patients

Abstract: ObjectiveTo ascertain the feasibility of using shear wave velocity (SWV) in assessing the stiffness of carotid plaque by supersonic shear imaging (SSI) and explore preliminary clinical value for such evaluation.Materials and MethodsSupersonic shear imaging was performed in 142 patients with ischemic stroke, including 76 males and 66 females with mean age of 66 years (range, 45–80 years). The maximum, minimum, and mean values of SWV were measured for 129 carotid plaques. SWVs were compared between echolucent an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 33 publications
0
30
0
3
Order By: Relevance
“…All studies scored an unknown or high risk of bias in at least one category. Seven studies (Ramnarine et al 2014b;Garrard et al 2015;Li et al 2016;Zhang et al 2016;Alis et al 2018;Shang et al 2018;Marlevi et al 2020) did not report whether they included patients randomly or consecutively, and one study reported they did not (Marais et al 2019). In addition, most studies (Li et al 2016;Zhang et al 2016;Lou et al 2017;Marais et al 2019) did not report whether the index test was interpreted without knowledge of the reference standard and vice versa.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies scored an unknown or high risk of bias in at least one category. Seven studies (Ramnarine et al 2014b;Garrard et al 2015;Li et al 2016;Zhang et al 2016;Alis et al 2018;Shang et al 2018;Marlevi et al 2020) did not report whether they included patients randomly or consecutively, and one study reported they did not (Marais et al 2019). In addition, most studies (Li et al 2016;Zhang et al 2016;Lou et al 2017;Marais et al 2019) did not report whether the index test was interpreted without knowledge of the reference standard and vice versa.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…In addition, most studies (Li et al 2016;Zhang et al 2016;Lou et al 2017;Marais et al 2019) did not report whether the index test was interpreted without knowledge of the reference standard and vice versa. Additionally, multiple studies (Ramnarine et al 2014b;Zhang et al 2016;Lou et al 2017;Shang et al 2018) used echogenicity as a reference standard in assessment of plaque vulnerability. However, echogenicity provides only an indication of plaque composition; it does not absolutely assess it.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, shear wave-based elastography techniques, such as shear wave elastography (SWE) and shear wave dispersion (SWD) have received wide attention for noninvasive assessment of elasticity and viscidity properties [8, 9]. This study was to assess the carotid TS and viscoelasticity by ultrasonic technologies and explored the relationship between them.…”
Section: Introductionmentioning
confidence: 99%